Knowledge Sharing Motivation, Behavior, and Creativity of Knowledge Workers in Virtual Organizations - Jian Jin; Sid Suntrayuth (Discrete Dynamics in Nature and Society)
Focusing on the basic research subject of “seeking effective ways to enhance knowledge workers’ creativity,” this paper has surveyed a total of 208 employees from 11 Chinese high-tech enterprises. Based on review and analysis of relevant literature, this paper has constructed a moderating effect model including mediating factors relying on the social cognitive theory and tested the model by hierarchical multiple regression. The results show that there is a significant positive correlation between knowledge sharing motivation and creativity of members in a virtual organization. Knowledge sharing behavior plays a partial mediating role between knowledge sharing motivation and creativity, and self-efficacy moderates the complete mediating effect of knowledge sharing behavior on the relationship between knowledge sharing motivation and creativity. These conclusions enrich the theory of the relationship between knowledge sharing motivation and creativity, and enable enterprises to understand the importance of employees’ knowledge sharing motivation and the ways to stimulate employees’ creativity by activating their knowledge sharing behavior.